Učenje vožnje s kolesom za otroke - Kodrin, Matej (Šport (Ljubljana), 2013)
The contribution presents a method for small children to learn to ride a bicycle. We defined some factors that affect successful learning and sought to find answers to the questions of when and how to start and which bicycle to use. We designed a programme for learning to ride a bicycle which consists of seven phases and teach the child to manage a bicycle. A special emphasis was given to play; we designed ten interesting games that help children improve their bike riding skills. The games are ranked by the level of complexity and each of them is described, including the purpose of the game and the required aids. We believe that many factors must be considered, such as the age or level of development of a child, his/her morphological characteristics and motor abilities as well as the size and type of bicycle (balance bike, tricycle, bicycle).
Keywords: child; children; cycling; kolesarjenje; learning to ride a bicycle; otroci; predšolska vzgoja; pre-school education; sport; šport; učenje vožnje